Analisis Rasio Aktivitas Untuk Menilai Kinerja Keuangan Pada PT. XL Axiata Tbk Tahun 2015-2019 - Muyasaroh, Muyasaroh; Nafilah, Nafilah (STAI La Tansa Mashiro, 2024)
The purpose of this study was to determine how the activity ratio analysis and to assess how the financial performance of PT. XL Axiata Tbk in 2015-2019. The method used in this research is a quantitative descriptive approach. The results of this study indicate that the activity ratio which includes Receivable Turn Over is 17.79 times, 32.20 times, 28.25 times, 16.04 times, 32.87 times. Days of Receivable are 20, 11, 13, 22, 11 days. Inventory Turn Over 298.64 times, 132.49 times, 159.63 times, 121.32 times, 336.86 times. Days of Inventory for 1, 2, 2 , 3, 1 day. Working Capital Turn Over 1.62 times, 1.00 times, 1.05 times, 1.25 times, 1.31 times. Fixed Assets Turn Over 0.46 times, 0.44 times, 0.46 times, 0.45 times, 0.45 times. Total Assets Turn Over 0.38 times, 0.38 times, 0.40 times, 0.39 times, 0.40 times. Overall, the financial performance of PT XL Axiata Tbk is considered not good. Keywords: Activity Ratio, Financial Performance.